Racism and Indigenous Adolescent Development: A Scoping Review. (3rd April 2022) - Uink, Bep; Bennett, Rebecca; Bullen, Jonathan; Lin, Ashleigh; Martin, Gregory; Woods, Jenna; Paradies, Yin
Abstract : Previous studies on the impacts of racism on adolescent development have largely overlooked Indigenous youth. We conducted a scoping review of the empirical literature on racism against Indigenous adolescents to determine the nature and scope of this research and to establish associations with developmental outcomes. Our literature search resulted in 32 studies with samples from the United States, Canada, Australia and New Zealand. Studies were limited to self‐reported experiences of racism and thus primarily focused on perceived discrimination. Quantitative studies found small to moderate effects of perceived discrimination on adolescent psychopathology and academic outcomes. Qualitative studies provided insight into structural forms of racism. We offer recommendations for future investigations into the impacts of overt and covert racism on Indigenous adolescents.